Effects of chondroitin sulfate oligosaccharides on osteoclast differentiation of RAW264 cells, and myotube differentiation of C2C12 cells - Hirofumi Uchiyama; Daisuke Muramatsu; Hideaki Higashi; Hiroshi Kida; Atsushi Iwai (PLoS ONE, 2023)
Chondroitin sulfate (CS) is a glycosaminoglycan, and CS derived from various animal species is used in drugs and food supplements to alleviate arthralgia. The CS is a high molecular weight compound, and hydrolysis of CS by intestinal microbiota is thought to be required for absorption in mammalians. Chondroitin sulfate oligosaccharides (Oligo-CS) are produced by hydrolysis with subcritical water from CS isolated from a species of skate, Raja pulchra for the improvement of bioavailability. The present study conducted in vitro experiments using murine cell lines, to compare the biological activities of Oligo-CS and high molecular weight CS composed with the similar disaccharide isomer units of D-glucuronic acid and N-acetyl-D-glucosamine (CS-C). The results show that Oligo-CS inhibits osteoclast differentiation of RAW264 cells significantly at lower concentrations than in CS. The cell viability of a myoblast cell line, C2C12 cells, was increased when the cells were grown in a differentiated medium for myotubes with Oligo-CS, where there were no effects on the cell viability in CS. These results suggest that in vitro Oligo-CS exhibits stronger bioactivity than high-molecular weight CS.